On the calibration of drill-string models based on hysteresis cycles data. (1st July 2020) - Lobo, D.M.; Ritto, T.G.; Castello, D.A.; de Souza, M.L.M.
Highlights: A mathematical model is developed to describe the dynamics of an experimental test-rig. A novel procedure is proposed to calibrate the model developed. The measured data used is obtained from a laboratory test-rig. The calibration procedure could calibrate hysteresis-cycles data. The new procedure proposed might be valuable to other systems with hysteresis. Graphical abstract: Abstract: The vibration of drill-strings is a common issue regarding drilling operations. Computational models are often used to predict drill-string dynamics but they must be properly calibrated before guiding field decisions. In this context, this paper proposes a model to describe the dynamics of an experimental test-rig and applies a novel procedure to calibrate this model. The model calibration is phrased as an optimization problem where the cost function takes into account the orientation of the hysteretic cycles, through complex combinations between torque on bit and weight on bit with the bit rotational speed. The measured data used to perform this analysis is obtained from a laboratory test-rig. The analyses shown in this paper indicate the feasibility of the proposed model and the effectiveness of the approach used for its calibration. The new procedure proposed in this paper might be valuable to other systems with hysteresis (e.g. bolt joint, shape memory alloy, electro-magnetic, polymer nanocomposites).